NANO COPPER VERSUS COPPER SULPHATE SUPPLEMENTATION IN BROILER DIETS – EFFECT ON GROWTH RESPONSE, CARCASS TRAITS AND COPPER RETENTION - Akeem A. Ayoola (Polish Journal of Natural Sciences, 2023)
A 42-day trial was conducted with 144 (arbor acre) day-old broiler chicks to evaluate the growth response and carcass yield of broiler chickens to dietary supplementation of copper sulphate and nano copper and consequently copper retention. Birds were divided into four groups and assigned to the dietary treatments; 250 ppm CuSO4, 225 ppm Cu-NP, 275 ppm Cu-NP supplementation and control (antibiotics). Data collected were subjected to one - way Analysis of Variance. Results indicated that birds fed dietary nano copper had similar (P < 0.05) growth and dress yield [%] compared to other groups. Supplemented birds at higher dosages (250 mg/kg and 275 mg/kg of CuSO4 and Cu-NP, respectively) exhibit high faecal copper excretion and retention in liver compared to the control group. The study therefore concludes that copper residue in faeces and liver increased with dietary copper supplementation, however, nano copper is better available to the birds than CuSO4. Hence, supplementation of 225 ppm of nano copper is recommended for less liver copper load and excretion.